Lacanian Reflections on the Neuropsychoanalysis Debate: From Epistemology to Ontology - John Dall'Aglio (The European Journal of Psychoanalysis, 2024)
While the neuropsychoanalytic field marches ahead, its critics continue to problematize the essential question of the discipline: how does neuroscience, a system of objective knowledge, contribute to psychoanalysis, a system of subjectivity? Critics charge neuropsychoanalysis with not providing a clear formula for toggling between neuroscience and psychoanalysis, leaving the field vulnerable to criticisms of theoretical imprecision. Lacanian and non-Lacanian critics alike warn that these epistemological missteps lead to harmful bio-reductionism. Taking these criticisms seriously, this paper reframes this debate from a Lacanian neuropsychoanalytic standpoint. Whereas the debaters disagree over the validity of neuropsychoanalytic epistemology, they leave (natural) ontology relatively unquestioned, implying a simply existing substrate. A Lacanian neuropsychoanalysis—rooted in the philosophical framework of Transcendental Materialism—problematizes the nature of this natural ontology. Beyond a Thing grasped from two divergent lenses, the ontological level itself is characterized by gaps, discontinuities, and antagonisms. Instead of (just) correlating neuroscientific and psychoanalytic concepts, this stance seeks connections at the limits or contradictions within epistemological frameworks. This antagonistic ontology fundamentally reframes the issues raised in the neuropsychoanalysis debate, opening a pathway for novel future bridges.
Keywords: Dual-aspect Monism; Transcendental Materialism; ontology; epistemology; neuroscience; Lacan; Solms